Detection of Lr19/Sr25 in segregating populations of wheat (Triticum aestivum L.) using robust molecular markers - Pal, Dharam; Bhardwaj, Subhash Chander; Khan, Hanif; Patial, Madhu; Yadav, Ram Niwas; Sharma, Pratima; Kumari, Shilpi (Journal of Cereal Research, 2021)
Marker assisted breeding (MAB) technology has been proved effective to transfer the genes of interest and also increased the accuracy of selection in wheat improvement programmes. The Agropyron elongatum derived 7D.7Ag translocation carrying Lr19/Sr25 is not only effective against leaf rust pathotypes but also effective against stem rust race Ug99 and its variants. Therefore, wheat breeding lines carrying Lr19/ Sr25 translocation segment have been developed worldwide. The present study was aimed for developing wheat genotypes with Lr19/ Sr25 using Xwmc221, PSY1-E1 and Gb DNA markers in segregating populations of wheat. We could infer that Xwmc221, PSY1-E1 and Gb are effective molecular markers to tag Lr19/Sr25 in segregating generations of wheat. The data also revealed consistency between host pathogen interaction (HPI) test and Xwmc221, PSY1-E1 and Gb molecular markers for selecting lines with Lr19/Sr25 in segregating generations. This work not only confirmed the robustness of the three Lr19/Sr25 markers but also demonstrated the application of both genotyping and phenotyping in making full-proof selection of superior progenies with gene of interest in wheat.